Effect of Moringa oleifera Leaf Meal on Growth Performance and Blood Parameters of Egg Type Chicken During Juvenile Growth - Voemesse , K.; Teteh, A.; Nideou, D.; N`nanle, O.; Gbeassor, M.; Decuypere, E.; Tona, K. (International Journal of Poultry Science, 2018)
Background and Objective: Medicinal plants are currently used as alternative to antibiotics growth promoters. However, their positive effect on livestock growth performance, particularly on poultry, depends on the rearing conditions and the birds’ lines. This study investigated the effect of different levels of Moringa oleifera leave meal (MOLM) on performance and serum biochemical parameters of egg-type chicken from one day old to 8 weeks of age. Methodology: A total of 450 days old chicken were randomly assigned to three treatment groups (M0, M1 and M3), 150 birds per treatment group and were respectively fed with diets containing 0, 1 and 3% of Moringa leaf. During experimental period, feed intake, body weight and feed conversion ratio were recorded weekly. At 5 weeks of age, 12 birds per group were slaughtered to collect blood, gizzard, pancreas, heart and liver. Blood serum concentrations in total protein, albumin, uric acid, calcium, magnesium and iron were also determined. Results: Results showed similarity between feed intake, liver relative weight while significant differences (p<0.05) between treated groups and the control one were observed on body weight, daily weight gain, feed conversion ratio and gizzard relative weight. In addition, total protein, albumin, calcium, magnesium and iron levels were significantly increased (p<0.05) in chickens fed MOLM as compared to control. The results also indicate that chickens of control diet group had higher blood uric acid level (p<0.05). However, no significant difference in phosphorus concentration was found between groups. Conclusion: During juvenile growth, MOLM did not affect feed intake, liver relative weight and phosphorus level. The leaves affect body weight, daily weight gain, feed conversion ratio and gizzard relative weight. Significantly differences were observed on total protein, albumin, calcium, iron and magnesium levels.